Hubungan Status Nutrisi dengan Kualitas Hidup pada Lansia Penderita Diabetes Mellitus Tipe 2 yang Berobat di Poli Penyakit dalam RSD Mardi Waluyo Blitar - Erni Setiyorini; Ning Arti Wulandari (STIKes Patria Husada Blitar, 2017)
Type 2 Diabetes Mellitus is mostly elderly. In the aging process, glucose tolerance decreases. The most common problem occurs in patients with DM is to maintain ideal body weight. Some elderly people have problems with excessive weight and some malnutrition. The condition of malnutrition in elderly with type 2 diabetes has an effect on physical and psychological function, both of these factors are important in the satisfaction of quality of life. The quality of life of DM patients is a feeling of satisfaction and happiness will live in general, especially with diabetes mellitus. The aims of this study was to determine the relationship between nutritional status and functional capacity with the quality of life of elderly people with diabetes mellitus type 2. The design in this study is correlational with cross sectional approach. Sampling technique of accidental sampling. Identify elderly people with type 2 diabetes in accordance with the inclusion criteria, then Data collection is done by weighing weight and measuring the height of elderly, filling the quality of life questionnaire, and functional capacity. Data analysis using Spearman Rank. The results showed that there was a significant relationship between nutritional status and functional capacity with quality of life of elderly people with type 2 diabetes, the correlation of each with r = 0,000 and r = 0.003. Expected For health workers to provide motivation to patients to maintain a good lifestyle so as to minimize complications and quality of life of the elderly either. For families to support and facilitate healthy lifestyles in elderly people with type 2 diabetes to achieve the most nutritional status and functional status according to age and ability.